Akuisisi Sinyal Electrocardiography (ECG) Berbasis Arduino - Rizki Fadilla; Putri Madona (Politeknik Caltex Riau, 2021)
Heart attack is still one of the leading causes of death worldwide. Much research has been done to make a portable and accurate ECG signal acquisition module as a solution to heart disease problems. This portable and easy-to-use module can be used by patients independently to find out as early as possible any disturbances in the heart's function. This ECG signal acquisition tool will generate ECG signals that will be utilized to record the patient's heart signal data. The tool consists of a biopotential circuit as a signal amplifier from the electrode sensor, then LPF filters and non-inverting amplifiers are added to eliminate noise and amplify the signal before entering a later stage. The testing was conducted on 3 subjects with 3 conditions: sitting, climbing stairs, and running. Test results showed the tool was able to display ECG signals at a fairly good PQRST interval, although noise still appeared to affect the signal. Meanwhile, Beat Per Minute (BPM) testing of each subject compared to the BPM calculation results manually resulted in a fairly low error rate of 3.52% for sitting conditions, 2.47% after climbing the stairs, and 3.73% after running.